Сhild-parent relationship as a predictor of youth's financial activity - N. E. Zhdanova; I. V. Vorobeva; M. S. Krivoshchekova; S. I. Velkova (Russian State Vocational Pedagogical University, 2020)
Introduction. The study of financial behaviour and human activity in relation to the management of material resources seems relevant both from the point of view of identifying potential risks of deviant behaviour patterns in this area, and identifying training opportunities for effective management of their own financial resources. The studies of financial behaviour of young people in conjunction with parent-child relationships are poorly presented in modern science and are conducted mainly abroad. Due to the lack of data, the value of the Russian research is great due to the high demand for scientific ideas about such relationship.The aim of the present research is to identify the interdependence between child-parent relationships and the financial activity of young people through the correlation of their models of financial behaviour, as well as the search for determinants of the activity of boys and girls in the system of parenting.Methodology and research methods. An empirical study was conducted on two related samples - youth representatives (young teenagers aged from 14 to 16 years old) and their parents. The total number of study participants was 144 people, of which 87 parents (57 women and 30 men) and 57 youth representatives (29 girls and 28 boys). For data collection, the authors compiled a questionnaire. This questionnaire contains two blocks: an assessment of the financial activity of the family and an assessment of the financial activity of youth. Also, the authors employed the methodology "Family Relationship Analysis" (by E. G Eidemiller, V. V. Yustitskis) and the questionnaire "Parent Behaviour and the Attitude of Children toward It" (by E. Schafer). Processing of the obtained data was carried out in the statistical package IBM SPSS Statistic 19.0. For mathematical and statistical analysis, the methods of descriptive statistics, cluster analysis, correlation analysis and regression analysis were used.Results and scientific novelty. As a result of an empirical study, two statistically significant regression models were constructed. According to the obtained models, some features of parent-child relationships really stimulate the financial activity and independence of youth. The groups of financially active and passive boys and girls are identified. It is established that these groups differ only in relation to their own assessments of parental impact by the mother.Practical significance of the work lies in the possibility of using the obtained data to form a scientific understanding of the genesis and mechanisms of formation of a person's financial activity, as well as in identifying target groups and developing effective methods for teaching financial literacy of the population.